The evolution of the meatal chamber in crocodyliforms - Montefeltro, Felipe C. [UNESP]; Andrade, Denis V. [UNESP]; Larsson, Hans C. E. (My University, 2016)
The unique outer ear of crocodylians consists of a large meatal chamber (MC) concealed by a pair of muscular earlids that shape a large part of the animal's head. This chamber is limited medially by the enlarged tympanic membrane. Yet, the anatomy of this distinctive and complex region is underexplored and its evolutionary history untraced. The osteology and soft tissues of the MC in extant crocodylians was analysed to describe it and establish osteological correlates within this region. A broad survey of the osteological correlates was conducted in major clades of fossil crocodyliforms to estimate evolutionary trends of the MC. The reorganization of the MC at the origin of crocodyliforms includes characters also present in more basal taxa such as 'sphenosuchians' as well as unique traits of crocodyliforms. Three major patterns are recognized in the MC of basal mesoeucrocodylians. The distinct 'thalattosuchian pattern' indicates that extensive modifications occurred in this clade of aquatic fossil crocodyliforms, even when multiple alternative phylogenetic positions are taken into account. Some traits already established in putative closely related clades are absent or modified in this group. The 'basal notosuchian/sebecian pattern' is widespread among basal metasuchians, and establishes for the first time characters maintained later in neosuchians and extant forms. The 'advanced notosuchian pattern' includes modifications of the MC possibly related to a terrestrial lifestyle and potentially a structure analogous to the mammalian pinna. The main variation in the MC of neosuchians is associated with the homoplastic secondary opening of the cranioquadrate passage. The inferred phylogenetic trends in the crocodyliform MC suggest the great anatomical disparity in this region followed a complex evolutionary pattern, and tympanic hearing played an important role in the origin and diversification of Crocodyliformes.
Keywords: Crocodyliformes; Outer-ear; Tympanic membrane